(untitled) (Research, Society and Development, 2021)
To evaluate the factors associated with the decline in hemoglobin in patients with CKD. This is a cross-sectional study, conducted with women undergoing hemodialysis, except for those with hemolytic diseases. The collection of biochemical and anthropometric data was carried out from the electronic medical records of the patients included in the research. 80% of the women were adults and the most prevalent chronic condition was Systemic Arterial Hypertension (75.65%). It was possible to verify that all the categories analyzed presented an average hemoglobin value below 12g /dL, indicating anemia as a problem in effect in the studied public. The factors that showed a statistically significant association with the lowest hemoglobin levels were: Hypertension, Diabetes mellitus and the shortest time on hemodialysis. The presence of other conditions in patients with CKD, such as diabetes, hypertension and shorter hemodialysis time, contribute to greater impairment of hemoglobin levels.